Gender Justice Dissemination via Afkaruna Official Instagram: Diseminasi Keadilan Gender melalui Instagram Afkaruna Official - Cahyati, Lili; BM, ST. Aisyah; Selo, Arham; Tasruddin, Ramsiah; Siagian, Haidir Fitra (Academia Open, 2026)
General Background: Social media has become a strategic medium for mass communication in disseminating gender justice issues. Specific Background: Instagram is utilized by Afkaruna Official to communicate gender justice based on Islamic feminist perspectives to diverse audiences. Knowledge Gap: Existing studies rarely analyze communication strategies, message representation, and audience reception within Islamic feminist digital activism. Aims: This study examines the urgency of dissemination, communication strategies, and audience responses. Results: Instagram serves as a strategic space shaped by persistent gender bias and low literacy. Strategies include optimized content distribution, persuasive education, visual storytelling, and inclusive Islamic framing. Audience responses are generally positive through likes, comments, and shares, although active dialogue remains limited. Novelty: The study integrates digital communication strategies with Islamic feminist perspectives in social media activism. Implications: The findings indicate that social media contributes to gender justice literacy and public awareness while requiring more participatory communication approaches. Highlights• Instagram operates as a discourse space connecting religious values with equality narratives• Content strategies rely on narrative depth, visual formats, and inclusive language• Audience engagement shows acceptance through symbolic interaction rather than discussion KeywordsGender Justice; Information Dissemination; Mass Communication; Social Media; Islamic Feminism